Impact of Radial Electrode Coverage on the Performance of Liquid-Deployed PMUTs: A Dynamic and Kinematic Study - Stephen Sammut; Edward Gatt; Ruben Paul Borg (Micromachines)
This paper highlights the optimisation of a key design parameter essential to the development of PMUTs, which are part of the transmitting components of microsensors. These microsensors are designed for use in the Structural Health Monitoring of reinforced concrete structures. Enhancing the effectiveness of the transmitting component allows for greater spacing between microsensors, which in turn reduces the number of devices needed to implement a full structural health monitoring system. PMUTs designed for integration into the pore solution of reinforced concrete structures need to operate effectively with liquid coupling fluids to ensure optimal sonic energy transfer into the structure. This paper outlines the techniques employed to optimize the central electrode’s percentage radial cover of the piezoelectric layer, in circular PMUTs resonating at around 100 kHz. This optimisation was achieved using Finite Element Modelling, laser vibrometry, and hydrophone experimental techniques. The results demonstrated that a radial electrode cover between 65 and 70% significantly enhances the kinematic and dynamic characteristics of a PMUT’s diaphragm when subjected to the excitation of a sine wave electrical signal. The paper also includes advanced time domain finite element analysis, through which the authors aimed to illustrate the diaphragm’s movements at various levels of radial electrode coverage.